Cuidando do paciente com Alzheimer: o impacto da doença no cuidador Caring for the Alzheimer's patient: the impact of the illness on the caregiver - Naira Dutra Lemos; Juliana Maria Gazzola; Luiz Roberto Ramos (Universidade de São Paulo, 2006)
OBJETIVO: Avaliar o impacto subjetivo da Doença de Alzheimer (DA) na vida dos cuidadores primários de idosos com esse diagnóstico. MÉTODO: Foi realizado um estudo transversal com 29 cuidadores de pacientes com DA. Os instrumentos utilizados foram: a Caregiver Burden Scale (CBS), um questionário para avaliação social do cuidador e um formulário para elaboração do perfil do paciente. Procedeu-se estatística descritiva simples, Coeficiente de Correlação de Pearson (r), Test T, para amostras independentes, e ANOVA, seguida do método de Bonferroni, a d" 0,05. RESULTADOS: A maioria dos cuidadores era do sexo feminino (89,7%), com idade média entre 48 e 58 anos, sendo 55,2% filhos, 27,6% cônjuges; e 55,2% com 8 anos de estudo. O escore médio global da CBS foi de 2,18. A média do escore total da CBS é maior nos cuidadores de pacientes restritos ao leito (p = 0,020). Os cuidadores com menor grau de escolaridade apresentaram maior escore total na CBS (p = 0,039). CONCLUSÕES: O impacto subjetivo da DA no cuidador foi considerado importante e depende de fatores como o seu nível de escolaridade e o grau de dependência dos pacientes. OBJECTIVE: To evaluate the subjective impact of Alzheimer's Disease (AD) on the lives of the primary family caregivers of patients suffering from said disease. METHOD: A cross analysis has been carried out among 29 caregivers of patients assisted. The used tools were the CBS, and a questionnaire to carry on a social survey on the caregivers and a formulary to perform an analysis on profile of the patient. Simple descriptive statistics, Pearson's Correlation Coefficient (r), T Test for independent samples and ANOVA were performed, followed by the Bonferroni method, a d" 0.05. RESULTS: Most of caregivers were women (89.7%) average age 58, 55.2% elderly's children, 27.6% couples, most of them having studied for over 8 years (55.2%), and 86.2% living with the elderly. The global average impact score on the subjective impact calculated by the CBS was 2.18. The total score average of the CBS is higher in caregivers of bed-restricted patients (p=0.020). Caregivers with a lower educational level had a higher total score in the CBS (p=0.039). CONCLUSIONS: The subjective impact of AD in the caregiver was deemed significant and subject to various factors, such as caregiver educational level and patient dependency level.